Effects of Discharge Parameters on the Thawing Characteristics and Physicochemical Properties of Beef in a Dielectric Barrier Discharge (DBD) System - Jie Zhang; Rui Zhao; Yaming Zhang; Huixin Wang; Zhiqing Song; Ru Xing; Jingli Lu; Changjiang Ding (Foods)
Traditional thawing techniques can cause certain losses to beef quality. Due to the increasing demand for high-quality beef, there is an urgent need to research new thawing techniques. Dielectric barrier discharge (DBD), as an innovative non-thermal thawing technology, still has a lot of work to be studied. In order to explore the influence of DBD on the thawing characteristics and quality of beef, different discharge parameters were used for thawing. The results show that voltage and needle distance have significant effects on ion wind speed and composition. Ion wind can improve the thawing rate, and the thawing time of DBD is 50% shorter than that of natural thawing. DBD improved the water-holding capacity, nutritional components, and color of beef, and the ordered structure of beef protein could be improved by 6.25% at most. The plasma emission spectrum shows that the plasma produced by DBD is mainly active substances of nitrogen and oxygen, which can reduce the fat oxidation of thawed beef and improve the quality of beef. This work provides the theoretical basis and practical guidance for deeply understanding the influencing parameters and thawing mechanism of DBD thawing technology.